HADH may be the target molecule of early vascular endothelial impairment in T2DM - Ye, Haowen; Wang, Ruxin; Wei, Jinjing; Wang, Ying; Wang, Lihong; Zhang, Xiaofang (Frontiers in Cardiovascular Medicine, 2022)
Background: Type 2 diabetes mellitus (T2DM) will significantly increase the risk of atherosclerosis (AS). Vascular endothelial cell dysfunction (VECD) is the foundation of AS. Early identification and intervention of VECD caused by T2DM can help us effectively delay or even suppress the occurrence of AS. Methods: We downloaded the gene expression profiles from the Gene Expression Omnibus (GEO). The differential expression genes (DEGs) were identified in R software and weighted gene co-expression network analysis (WGCNA) was performed to further screen the target genes. In addition, we used the receiver operating characteristic curve (ROC curve) to verify the diagnostic efficiency of target genes. Finally, target genes were validated by quantitative polymerase chain reaction (qPCR). Results: Four target genes (CLUH, COG4, HADH and MPZL2) were discovered in early vascular endothelial impairment caused by T2DM through differential expression analysis and WGCNA. The ROC curve of target genes showed that HADH had the best diagnostic efficacy in VECD and AS. qPCR showed that the mRNA level expression of HADH and MPZL2 were decreased in human coronary artery endothelial cells (HCAECs) treated with high glucose and palmitic acid. Conclusion: HADH may be the target gene in early VECD caused by T2DM.